Medical phenome of musicians: an investigation of health records collected on 9803 musically active individuals. Issue 1 (19th August 2021) - Niarchou, Maria; Lin, George T.; Lense, Miriam D.; Gordon, Reyna L.; Davis, Lea K.
Abstract: Previous studies suggest that musicians may be at higher risk for a set of medical problems; however, this literature has been limited by relatively small sample sizes, self‐reports, and lack of controls. To address such limitations, we examined trends in the medical care of musicians in an Electronic Health Record database. On the basis of a collection of keywords and regular expressions in the patients' clinical notes, we identified 9803 "musicians" that we matched for sex, median age (across the medical record), ethnicity, race, the length of record, and the number of visits with 49, 015 controls. We fitted 1263 logistic regression models to determine whether the phenotype was correlated with musicianship. Two hundred fifty‐seven phenotypes were more prevalent in musicians than controls after Bonferroni adjustment ( P < 7.6 × 10 –6 ), including diseases of the larynx and vocal cords (OR = 2.32 (95% CI: 2.25–2.40)), and hearing loss (OR = 1.36 (95% CI: 1.32–1.39)). Fifteen phenotypes were significantly more prevalent in controls than musicians, including coronary atherosclerosis (OR = 0.91 (95% CI: 0.89–0.94)). Although being a musician was related to many occupational health problems, we identified protective effects of musicianship in which certain disorders were less common in musicians than in controls, indicating that active musical engagement could have health benefits analogous to athletic engagement. Abstract : We conducted the first phenome‐wide association studies of musicians using an electronic health record framework in over 80, 000 individuals and found both the risk and protective associations with many medical disorders. These included medical complaints involving the musculoskeletal system, the respiratory, endocrine, and metabolic systems, as well as mental health problems. We also identified a number of protective effects by observing diagnoses, such as cardiovascular disease and respiratory and renal failure, which were less common in musicians than in controls, in line with the literature indicating that active musical engagement has similar health benefits to athletic engagement.